2015
DOI: 10.1002/lary.25316
|View full text |Cite
|
Sign up to set email alerts
|

Value and discriminative power of the seven‐item eustachian tube dysfunction questionnaire

Abstract: 3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 14 publications
4
71
1
4
Order By: Relevance
“…In another study, Roeyen et al [5] translated this questionnaire into Dutch and assessed its validity. They found an area under the curve in the ROC analysis for the obstructive ET group of 95%, confirming its excellent discriminant validity for the healthy control group; however, it was unable to discriminate the pathology of ET obstructive or patulous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Roeyen et al [5] translated this questionnaire into Dutch and assessed its validity. They found an area under the curve in the ROC analysis for the obstructive ET group of 95%, confirming its excellent discriminant validity for the healthy control group; however, it was unable to discriminate the pathology of ET obstructive or patulous.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was validated and translated into several languages, such as German and Dutch. [4,5] In this study, we aimed to identify the value and discriminative power of the validated translation of the ETDQ-7 in a Turkish speaking population with and without ETD. To prevent the potentially confusing distribution of recent questionnaires that are not comparable to those available in the literature, a rigorous adaptation process is required, and mere translation alone is not adequate.…”
mentioning
confidence: 99%
“…McCoul et al [4] reported their ETDQ-7 to reliably discriminate between patients with obstructive ET dysfunction and healthy controls. However, Van Roeyen et al [5] later demonstrated that ETDQ-7 (even without the item autophony) cannot discriminate between obstructive and patulous ET dysfunction [5,6] . ETDQ-7 can thus assess symptom severity, but still, expert opinion is essential for discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline ETDQ-7 scores in the present patient population were previously compared with those in the control group by our group [5] .…”
Section: Control Groupmentioning
confidence: 99%
See 1 more Smart Citation